Time Use, Emotional Well-Being, and Unemployment: Evidence from Longitudinal Data - Krueger, Alan B; Mueller, Andreas I (American Economic Review, 2012)
This paper provides new evidence on the time use and emotional well-being of unemployed individuals in the weeks before and after starting a new job. The major findings are: (1) time spent on home production drops sharply at the time of re-employment, even when controlling for individual fixed effects; (2) time spent on leisure-related activities, which the unemployed find less enjoyable, drops on re-employment, but less so when controlling for individual fixed effects; (3) the unemployed report higher levels of sadness during specific episodes of the day than the employed; and (4) sadness decreases abruptly at the time of re-employment.